Central nervous system metastases of lung adenocarcinoma harboring EGFR-activating mutations: survival results from a multidisciplinary approach, including EGFR-TKIs - Guilherme Harada; Renata Rodrigues da Cunha Colombo Bonadio; Guilherme Nader Marta; Debora Zachello Recchimuzzi; Gilberto de Castro (Brazilian Journal of Oncology)
Objectives: Central nervous system (CNS) metastases are frequent in advanced lung adenocarcinomas harboring EGFR-activating mutations. However, the best treatment approach must be defined. We aimed to evaluate the effectiveness of a multidisciplinary approach for CNS metastases in patients previously untreated with EGFR tyrosine kinase inhibitors (EGFRTKIs). Methods: We performed a retrospective analysis of EGFR-TKI naïve patients with CNS metastases from lung adenocarcinomas harboring EGFR-activating mutations treated in a Brazilian academic cancer center. Data were collected from electronic records. Overall survival (OS) and progression-free survival (PFS) curves were estimated using the Kaplan-Meier method and compared by logrank test. Cox model was used to evaluate prognostic factors. Results: 35 consecutive patients were included. Treatment included an EGFR-TKI (erlotinib or gefitinib) for all patients, whole brain radiation therapy for 26 patients, stereotactic radiosurgery for 2 patients, and surgery for 8 patients. Median PFS and OS were 8.2 and 11.9 months, respectively. In a multivariable analysis, poor Eastern Cooperative Oncology Group performance status (3-4 vs 0-2) was associated with inferior OS (HR 2.86; 95% CI 1.12-6.74; p=0.016), while radiation therapy to treat brain lesions (yes vs no) showed a trend towards improved OS (HR 0.40; 95% CI 0.15-1.06; p=0.066). No difference was seen between upfront and salvage radiation therapy to the brain. Conclusions: A multidisciplinary treatment approach, including an EGFR-TKI, allowed promising outcomes for patients with CNS metastases of lung adenocarcinoma harboring EGFR-activating mutations, but the small number of patients here studied precludes definitive conclusions. Although radiation therapy to treat brain metastases has an important role, the best treatment sequence remains unclear. Currently, the approach must be individualized, considering patient characteristics, tumor biology and healthcare resources availability.